Predictive analytics with Excel LiveLessons : (sneak peek video training) - Carlburg, Conrad (Que, 2014)
"Predictive Analytics with Excel LiveLessons provides over 5 hours of video instruction. The movie Moneyball made predictive analytics famous. Now you can apply the same techniques to help your business win. These training videos show you how!"--Resource description page.